Perceived everyday discrimination and psychological distress: does social support matter? - Ajrouch, Kristine J. (Ethn Health, 2010)
OBJECTIVES. We investigate the association between perceived everyday discrimination and psychological distress among urban African-American women with young children (under 6 years) living in low-income neighborhoods. Specifically, we examine whether instrumental and emotional social support moderates the association between perceived everyday discrimination and psychological distress. DESIGN. The data come from the Detroit Dental Health Project, a two-stage area probability sample representative of low-income African-American children in the city of Detroit. The analysis focuses on 969 female caregivers of young children. A series of hierarchical regression analyses were performed to examine the role of social support in the link between perceived everyday discrimination and psychological distress, with appropriate adjustments for the complex sample design. RESULTS. Both moderate and high frequency levels of discrimination were associated with higher levels of psychological distress after controlling for age, education, income, and self-rated health. There was a main effect of emotional support so that availability of emotional support was associated with less psychological distress. Instrumental support exerted a buffering effect to mitigate the negative influence of moderate levels of perceived discrimination on psychological distress. CONCLUSION. Findings suggest that instrumental social support provides some protection from everyday stress. Social support, however, does not offset the impact of acute stress caused by frequent perceptions of everyday discrimination.